A novel dual MEK/PDK1 inhibitor 9za retards the cell cycle at G0/G1 phase and induces mitochondrial apoptosis in non-small cell lung cancer cells - Rangru Liu; Zutao Yu; Zhuo Chen; Danqi Liu; Fengying Huang; Qianbin Li; Gaoyun Hu; Xinan Yi; Xi Li; Honghao Zhou; Zhaoqian Liu (PeerJ, 2020)
Background A novel dual MEK/PDK1 inhibitor named 9za has been synthesized by our research team. Preliminary study showed that 9za possessed potent cytotoxicity and proapoptosis in non-small cell lung cancer (NSCLC) cells. Nevertheless, the precise underlying mechanism is vague. Methods In this work, we adopted the MTT assay, the Cell Cycle Detection Kit, and the JC-1 staining assay to detect the cell viability, the cell cycle distribution and the mitochondrial membrane potential (MMP), respectively. Cell apoptosis was measured by the morphology observation under a light microscope, Annexin V-FITC/propidium iodide (PI) apoptosis detection and the colorimetric TUNEL assay. Western blot was used to monitor the cell cycle-, apoptosis-related proteins and relevant proteins involved in the signaling pathways. Results The MTT assay demonstrated that 9za sharply decreased the viability of NSCLC cells. Cell cycle analysis revealed that low concentrations of 9za arrested the cell cycle at the G0/G1 phase , which was further confirmed by the decreased levels of Cyclin D1, cyclin-dependent kinase 4 (CDK4) and cyclin-dependent kinase 6 (CDK6). Additionally, morphological observations, Annexin V-FITC/propidium iodide (PI) apoptosis analysis and TUNEL assays indicated that high concentrations of 9za induced cell apoptosis. Furthermore, the JC-1 staining assay revealed that the mitochondrial membrane potential was downregulated following 9za exposure. Western blot also showed that 9za markedly decreased the expression levels of total Bcl-2, Cytochrome C in the mitochondria and BCL2 associated X (BAX) in the cytoplasm. However, the levels of BAX in the mitochondria, Cytochrome C in the cytoplasm, active caspase-9, active caspase-3 and cleaved–PARP showed the opposite changes. Moreover, the dose-dependent decreased phosphorylation levels of PDK1, protein kinase B (Akt), MEK and extracellular signal regulated kinase 1/2 (ERK1/2) after 9za treatment verified that 9za was indeed a dual MEK/PDK1 inhibitor, as we expected. Compared with a single MEK inhibitor PD0325901 or a single PDK1 inhibitor BX517, the dual MEK/PDK1 inhibitor 9za could strengthen the cytotoxic and proapoptotic effect, indicating that the double blocking of the MEK and PDK1 signaling pathways plays stronger cell growth inhibition and apoptosis induction roles than the single blocking of the MEK or PDK1 signaling pathway in NSCLC cells. Our work elucidated the molecular mechanisms for 9za as a novel drug candidate against NSCLC.